Chest radiograph characteristics in COVID-19 infection and their association with survival. (2021) - Colman, Jordan; Zamfir, Georgiana; Sheehan, Frances; Berrill, Max; Saikia, Sujoy; Saltissi, Felicity
Abstract: Purpose: This study aims to systematically grade CXRs of COVID-19 patients to find associations between CXR (chest radiographs) characteristics and clinical outcomes. Methods: A retrospective review and grading of CXRs in 161 COVID-19 positive patients was caried out in this single centre study. CXR changes primarily constituted that of presence or absence of ground glass opacification (GGO) or consolidation and their distribution across both lung fields. We used two grading systems normal/ mild/ moderate/ severe grading and a numeric 0−8 grading system. We defined mild severity as up to 25 % lung involvement, moderate as 25–62.5 % and severe as 62.5–100% lung involvement. Results: Peripheral GGO in lower +/- mid zones of the lungs is the most common finding. Mid zone and perihilar GGO is associated with increased mortality. We additionally show that CXRs have a higher severity score in the non-survivor group and a CXR graded as severe has a relative risk ratio for mortality of 3.28. Finally, we describe the change in CXR severity with length of symptoms, finding 42.3 % of CXR were normal in the first 2 days of symptoms and 0% at 13 days. Conclusion: Using a systematic approach to reviewing and grading CXRs in Covid-19 positive patients we clearly demonstrate that grading, location of airspace abnormalities and rate of CXR changes are related to clinical outcome.